Reversible hydrophilic / hydrophobic magnetic biomass foam material as well as preparation method and application thereof
By preparing reversible/hydrophobic magnetic biomass foam materials, the problem of treating multiple pollutants in complex industrial wastewater is solved, and the pollutant separation effect with high efficiency and low energy consumption is achieved, which is suitable for industrial wastewater treatment.
Patent Information
- Application Number
- CN202510751211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-08-15
AI Technical Summary
The prior art cannot effectively treat complex industrial wastewater with hydrophilic and hydrophobic pollutants. The traditional material preparation method is complex, has high energy consumption and a single function.
Nanocellulose was prepared by zinc chloride/phosphoric acid/ammonium dihydrogen phosphate three-component eutectic solvent for treatment of biomass waste, combined with titanium dioxide, magnetic ferrotetraoxide and silane modified solutions, and reversible/hydrophobic magnetic biomass foam materials were prepared by one-step method of normal pressure foaming and low-temperature drying, and performance switching was achieved using water/ethanol solvent to regulate the interface groups.
It has achieved efficient separation of pollutants in the oil-water mixing system under mild conditions, with a removal rate of up to 99.1%, reducing preparation energy consumption and complexity, low material density, and is suitable for industrial wastewater treatment.
Smart Images

Figure CN120479392A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sewage treatment, and in particular to a reversible hydrophilic / hydrophobic magnetic biomass foam material, a preparation method and application thereof. Background Art
[0002] Current industrial wastewater has a complex composition, containing both hydrophilic (such as heavy metal ions and dye molecules) and hydrophobic (such as oils and organic solvents) pollutants. Traditional adsorbent material preparation methods are complex and limited in functionality, targeting only a single type of pollutant. They can only adsorb and photocatalytically treat hydrophilic pollutants, or only adsorb and remove hydrophobic pollutants. These materials are unable to effectively remove the diverse pollutants found in the complex environment of actual industrial wastewater.
[0003] The existing technologies mostly prepare functional materials through methods such as hydrothermal reaction and freeze drying, which have problems such as high energy consumption, complex process, and the need for toxic modification reagents. For example, the “Preparation method and application of a magnetically responsive multifunctional super-hydrophobic biomass aerogel” disclosed in Chinese patent CN119186420A is complex in process and requires step-by-step freeze drying and then vacuum drying, which cannot achieve dynamic switching of hydrophilic / hydrophobic properties; the “A composite photocatalytic sewage treatment material and its preparation method” disclosed in Chinese patent CN100351011C has photocatalytic properties and superparamagnetism, but it is only applicable to hydrophilic pollutants, and the preparation process relies on high-temperature heat treatment (450~500℃). Therefore, there is an urgent need for a multifunctional material with simple process, adjustable function, and adaptability to complex wastewater environments. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a reversibly hydrophilic / hydrophobic magnetic biomass foam material, its preparation method, and application. The magnetic biomass foam material uses a three-component low eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate to treat biomass waste to prepare nanocellulose. A gel-like cellulose suspension is obtained at room temperature. Titanium dioxide, magnetic ferroferric oxide, and a silane-modified solution are introduced, and then a methyltrimethoxysilane / tetramethoxysilane copolymer emulsion is added. The material is prepared in a single step using a normal pressure foaming process and low-temperature gradient drying. The preparation method is simple, and under mild conditions, the interfacial groups can be regulated by water / ethanol solvents to achieve on-demand switching of the hydrophilic / hydrophobic properties of the magnetic biomass foam material, effectively separating pollutants from oil-water mixed systems.
[0005] The first aspect of the present invention provides a method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material, comprising the following steps: S1. Grinding biomass waste into short fibers, then treating them with a three-component deep eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate at room temperature to prepare nanocellulose, filtering and washing them, soaking them in deionized water, and then stirring them to form a stable gel-like fiber suspension; S2. Add polyvinyl alcohol to deionized water and dissolve the mixture in a water bath to obtain a polyvinyl alcohol solution; add chitosan to the acetic acid solution, dissolve the mixture and stir to obtain a chitosan solution; S3, reacting methyltrimethoxysilane / tetramethoxysilane in a ratio of 1:10 to 10:1 at 300 r / min, 30°C, and pH = 9 for 1 h to prepare a methyltrimethoxysilane / tetramethoxysilane copolymer emulsion with a concentration of 5%; S4. Place the gel-like fiber suspension obtained in S1, the polyvinyl alcohol solution obtained in S2, and the chitosan solution obtained in S2 in a conical flask, add sodium dodecyl sulfate, titanium dioxide, and ferrosoferric oxide, stir to foam, then add the methyltrimethoxysilane / tetramethoxysilane copolymer emulsion obtained in S3 and continue stirring, pour the completely foamed wet foam into a mold, let it stand at room temperature, and then dry to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material; by alternately using water and ethanol for solvent exchange at 80°C, the reversible hydrophilic / hydrophobic switching of the magnetic biomass foam material is achieved.
[0006] As an optimization, the fiber content of the biomass waste in S1 is 50% to 85%, and the biomass waste is ground into 60-80 mesh short fibers.
[0007] As an optimization, the molar ratio of the zinc chloride / phosphoric acid / ammonium dihydrogen phosphate three-component deep eutectic solvent in S1 is 1:0.3:1 to 1:0.3:6.
[0008] As an optimization, the S1 was filtered and washed and then immersed in 200 mL of deionized water for 24 h, and then stirred at 2000-4000 r / min for 10-30 min to form a stable gel-like fiber suspension.
[0009] As an optimization, 2-8 g of polyvinyl alcohol in S2 is added to deionized water at a ratio of 1:8-1:20, and the solution is dissolved in a water bath at 90° C. at a rotation speed of 500 r / min to obtain a polyvinyl alcohol solution.
[0010] As an optimization, in S2, 0.2-1 g of chitosan was added to 50 mL of 2% acetic acid solution, dissolved and stirred for 30 min to obtain a chitosan solution.
[0011] As an optimization, in S4, the fiber suspension obtained from S1, the polyvinyl alcohol solution obtained from S2, and the chitosan solution obtained from S2 are placed in a conical flask, sodium dodecyl sulfate, titanium dioxide, and ferrosoferric oxide are added, and stirred to foam, and then the methyltrimethoxysilane / tetramethoxysilane copolymer emulsion with a concentration of 5% obtained from S3 is added and continued to be stirred, and the completely foamed wet foam is poured into a mold, allowed to stand at room temperature, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material; under mild conditions, water and ethanol are alternately used for solvent exchange to achieve reversible hydrophilic / hydrophobic switching of the magnetic biomass foam material.
[0012] As an optimization, in S4, the fiber suspension obtained by S1, the polyvinyl alcohol solution obtained by S2, and the chitosan solution obtained by S2 are placed in a 500 mL conical flask, 0.2~1.0 g of sodium dodecyl sulfate, 0.5~3.5 g of titanium dioxide and 1~5 g of ferrosoferric oxide are added, and stirred at 3000 r / min for 15~30 min to make it foam, and then 20~50 g of 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion obtained by S3 is added and continued to be stirred for 10 min. The completely foamed wet foam is poured into a mold, allowed to stand at room temperature for 30 min, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material; by alternately using water and ethanol for solvent exchange at 80°C, the reversible hydrophilic / hydrophobic switching of the magnetic biomass foam material is achieved.
[0013] The second aspect of the present invention provides a reversible hydrophilic / hydrophobic magnetic biomass foam material prepared by the above preparation method.
[0014] A third aspect of the present invention provides an application of the above-mentioned reversibly hydrophilic / hydrophobic magnetic biomass foam material in sewage treatment.
[0015] The beneficial effects of the present invention are: 1. The present invention uses a three-component low eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate to treat biomass waste to prepare nanocellulose. Compared with conventional treatment methods, the solvent can selectively destroy the hydrogen bonds on the cellulose surface that are difficult to access without dissolving or degrading the cellulose by releasing a large amount of hydrogen ions and strong hydrogen bond molecular scissors effect, thereby successfully separating the nanocellulose from the cellulose. The advantage of this method is that it does not require high-temperature heating, can effectively reduce energy consumption and equipment requirements, achieves a cellulose extraction rate of up to 90%, and ensures recyclability and environmental friendliness. The present invention obtains a cellulose suspension at room temperature, introduces titanium dioxide, magnetic ferroferric oxide and silane modification solution, utilizes a normal pressure foaming process, and low-temperature gradient drying in one step to prepare a magnetic biomass foam material. The process is simple, does not require additional toxic modification reagents and complex equipment support, and is convenient for industrial promotion.
[0016] 2. The present invention modifies the surface of nanocellulose with silica during the foaming process by adding methyltrimethoxysilane / tetramethoxysilane copolymer emulsion. Under mild conditions (80°C), the silica surface groups can undergo a reversible esterification reaction through solvent exchange between water and ethanol. This process does not require complex chemical modification, and the solvent can be recycled, greatly reducing the preparation cost.
[0017] 3. The present invention can regulate the interfacial groups through water / ethanol solvents under mild conditions to achieve on-demand switching of the hydrophilic / hydrophobic properties of the magnetic biomass foam material. The water contact angle can be switched from 0 to 150 degrees, which can efficiently separate pollutants in oil-water mixed systems and effectively remove hydrophilic / hydrophobic pollutants in complex components of industrial wastewater.
[0018] 4. The magnetic biomass foam material prepared by the present invention has a low density (0.03~0.07 g / cm 3 The oil adsorption capacity can reach 37.2 g / g, and the organic pollutant removal rate can reach up to 99.1%. The preparation method is simple and has strong application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The following is a further description of a reversible hydrophilic / hydrophobic magnetic biomass foam material, its preparation method and application in conjunction with the accompanying drawings: Figure 1 This is a contact angle diagram of a water droplet of the reversibly hydrophilic / hydrophobic modified magnetic biomass foam material according to Example 1 of the present invention; Figure 2 This is a contact angle diagram of a water droplet of the reversibly hydrophilic / hydrophobic modified magnetic biomass foam material according to Example 2 of the present invention; Figure 3 This is a contact angle diagram of a water droplet of the reversibly hydrophilic / hydrophobic modified magnetic biomass foam material according to Example 3 of the present invention; Figure 4 This is a contact angle diagram of a water droplet of the reversibly hydrophilic / hydrophobic modified magnetic biomass foam material of Comparative Example 1 of the present invention; Figure 5 This is a contact angle diagram of a water droplet of the magnetic biomass foam material of Comparative Example 2 of the present invention; Figure 6 This is a contact angle diagram of a water droplet of the magnetic biomass foam material of Comparative Example 3 of the present invention; Figure 7 This is a picture of the embodiment 1 of the present invention on the petals and a picture of it being attracted by a magnet; Figure 8 This is a real picture of Example 2 of the present invention on the petals. DETAILED DESCRIPTION
[0020] The present application is further described in detail below in conjunction with the accompanying drawings and implementation methods. It is particularly pointed out that the experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used in the following preparation examples and examples are all commercially available unless otherwise specified. In addition, the following implementation methods are only used to illustrate the present application, but do not limit the scope of the present application. Similarly, the following implementation methods are only some of the implementation methods of the present application and not all of the implementation methods. All other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application. Example
[0021] First, sugarcane bagasse was ground into 60-mesh short fibers and then treated with a three-component low eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate with a molar ratio of 1:0.3:1 at room temperature to prepare nanocellulose. After filtration and washing, the fibers were immersed in 200 mL of deionized water for 24 h and then stirred at 2000 r / min for 20 min to form a stable gel-like fiber suspension. 2 g of polyvinyl alcohol was added to deionized water at a ratio of 1:8 and dissolved in a water bath at 90°C at a speed of 500 r / min to obtain a polyvinyl alcohol solution. 0.3 g of chitosan was added to 50 mL of 2% acetic acid solution, dissolved and stirred for 30 min to obtain a chitosan solution. Methyltrimethoxysilane / tetramethoxysilane were reacted at a ratio of 1:10 at 300 r / min, 30°C, and pH = 9 for 1 h to prepare a 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion. The fiber suspension, polyvinyl alcohol solution, and chitosan solution were then placed in a 500 mL conical flask. 0.3 g of sodium dodecyl sulfate, 0.5 g of titanium dioxide, and 1.5 g of ferrosoferric oxide were added. The mixture was stirred at 3000 rpm for 15 minutes to allow foaming. 25 g of a 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion was then added and stirred for another 10 minutes. The fully foamed foam was poured into a mold, allowed to stand at room temperature for 30 minutes, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam. The reversible hydrophilic / hydrophobic switching of the magnetic biomass foam was achieved by alternating solvent exchange between water and ethanol at 80°C.
[0022] Using a contact angle meter, the water drop contact angle of the magnetic biomass foam material was measured with water, and the measured contact angle of the material surface to water was 141.5 degrees. Example
[0023] First, the eucalyptus processing residue was ground into 80 mesh short fibers, and then treated with a three-component low eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate with a molar ratio of 1:0.3:4 to prepare nanocellulose at room temperature. After filtration and washing, it was immersed in 200 mL of deionized water for 24 h and then stirred at 3000 r / min for 30 min to form a stable gel-like fiber suspension; 6 g of polyvinyl alcohol was added to deionized water at a ratio of 1:12 and dissolved in a water bath at 90°C at a speed of 500 r / min to obtain a polyvinyl alcohol solution; 0.5 g of chitosan was added to 50 mL of 2% acetic acid solution, dissolved and stirred for 30 min to obtain a chitosan solution; methyltrimethoxysilane / tetramethoxysilane were reacted at a ratio of 5:1 at 300 r / min, 30°C, and pH = 9 for 1 h to prepare a 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion. The fiber suspension, polyvinyl alcohol solution, and chitosan solution were then placed in a 500 mL conical flask, and 0.5 g of SDS, 2.0 g of TiO₂, and 1.0 g of Fe₃O₄ were added. The mixture was stirred at 3000 rpm for 15 minutes to allow foaming. 30 g of a 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion was then added and stirred for another 10 minutes. The fully foamed foam was poured into a mold, allowed to stand at room temperature for 30 minutes, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material. The reversible hydrophilic / hydrophobic switching of the magnetic biomass foam was achieved by alternating solvent exchange between water and ethanol at 80°C.
[0024] Using a contact angle meter, the water drop contact angle of the magnetic biomass foam material was measured with water, and the measured contact angle of the material surface to water was 152.5 degrees. Example
[0025] First, corn straw was ground into 80-mesh short fibers and then treated with a three-component low eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate in a molar ratio of 1:0.3:6 at room temperature to prepare nanocellulose. After filtration and washing, the fibers were immersed in 200 mL of deionized water for 24 h and then stirred at 3000 r / min for 30 min to form a stable gel-like fiber suspension. 8 g of polyvinyl alcohol was added to deionized water at a ratio of 1:20 and dissolved in a water bath at 90°C at a speed of 500 r / min to obtain a polyvinyl alcohol solution. 1.0 g of chitosan was added to 50 mL of 2% acetic acid solution, dissolved and stirred for 30 min to obtain a chitosan solution. Methyltrimethoxysilane / tetramethoxysilane were reacted at a ratio of 8:1 at 300 r / min, 30°C, and pH = 9 for 1 h to prepare a 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion. The fiber suspension, polyvinyl alcohol solution, and chitosan solution were then placed in a 500 mL conical flask, and 0.8 g of SDS, 1.5 g of TiO₂, and 2.0 g of Fe₃O₄ were added. The mixture was stirred at 3000 rpm for 25 minutes to allow foaming. 30 g of a 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion was then added and stirred for another 10 minutes. The fully foamed foam was poured into a mold, allowed to stand at room temperature for 30 minutes, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material. The reversible hydrophilic / hydrophobic switching of the magnetic biomass foam was achieved by alternating solvent exchange between water and ethanol at 80°C.
[0026] Using a contact angle meter, the water drop contact angle of the magnetic biomass foam material was measured with water, and the measured contact angle of the material surface to water was 147.2 degrees.
[0027] Comparative Example 1 Different from Example 1, Comparative Example 1 did not use a three-component deep eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate with a molar ratio of 1:0.3:1 to prepare nanocellulose, and the other step conditions were the same as those in Example 1.
[0028] Using a contact angle meter, the water drop contact angle of the magnetic biomass foam material was measured with water, and the measured contact angle of the material surface to water was 98.9 degrees.
[0029] Comparative Example 2 The difference from Example 1 is that in Comparative Example 2, 30 g of 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion was not added, and the other step conditions were the same as those in Example 1.
[0030] The water drop contact angle of the magnetic biomass foam material was measured using a contact angle meter. The water contact angle of the material surface was found to be 0 degrees, indicating that the surface of the material in Comparative Example 2 was hydrophilic.
[0031] Comparative Example 3 The difference from Example 1 is that in Comparative Example 3, water and ethanol were not alternately used for solvent exchange at 80° C., and the other step conditions were the same as those in Example 1.
[0032] The water drop contact angle of the magnetic biomass foam material was measured using a contact angle meter. The water contact angle of the material surface was found to be 0 degrees, indicating that the surface of the material in Comparative Example 3 was hydrophilic.
[0033] The performance test results are shown in the following table: As can be seen from the table above, Comparative Example 1, which did not use the zinc chloride / phosphoric acid / ammonium dihydrogen phosphate three-component eutectic solvent to prepare nanocellulose, resulted in large fibers, a higher density, lower porosity, and poorer adsorption properties. Comparative Example 2, which did not add the methyltrimethoxysilane / tetramethoxysilane copolymer emulsion, produced a magnetic biomass foam material that was only hydrophilic. Comparative Example 3, which did not alternate between water and ethanol at 80°C for solvent exchange, produced a hydrophilic magnetic biomass foam material with minimal changes in performance. It can be seen that the reversible hydrophilic / hydrophobic magnetic biomass foam material and its preparation method provided by the present invention utilize a three-component low eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate to treat biomass waste to prepare nanocellulose, and by releasing a large amount of hydrogen ions and strong hydrogen bond molecular scissor effect, the hydrogen bonds that are difficult to access on the cellulose surface are selectively destroyed without dissolving or degrading the cellulose, and the nanocellulose is successfully separated from the cellulose. By adding methyltrimethoxysilane / tetramethoxysilane copolymer emulsion, the surface of the nanocellulose is modified with silica during the foaming process. The nanocelluloses are connected to each other by hydrogen bonds and intertwined to form a fibrous network structure. After cross-linking with polyvinyl alcohol and chitosan, the micro-nano pore structure of the foam material is supported to a certain extent by titanium dioxide and ferrous oxide, maintaining the stability of the micropores, thereby increasing the porosity of the magnetic biomass foam material and reducing the density. Under mild conditions, the silica surface groups can undergo a reversible esterification reaction through solvent exchange of water and ethanol. This process does not require complex chemical modification, and the solvent can be recycled. Comparing Example 1 and Example 2, it can be seen that when the amount of titanium dioxide added is too high, it will form aggregates on the fiber surface, affecting the photocatalytic performance and reducing the removal rate of organic pollutants.
[0034] In summary, the zinc chloride / phosphoric acid / ammonium dihydrogen phosphate three-component eutectic solvent utilized in the present method selectively destroys the inaccessible hydrogen bonds on the cellulose surface in biomass waste, achieving a cellulose extraction rate of up to 90%. High-temperature heating is not required during the process, effectively reducing energy consumption and equipment requirements while ensuring recyclability and environmental friendliness. A methyltrimethoxysilane / tetramethoxysilane copolymer emulsion is added during the foaming process to modify the nanocellulose surface with silica. Under mild conditions (80°C), a solvent exchange between water and ethanol allows the silica surface groups to undergo a reversible esterification reaction. This process does not require complex chemical modification, and the solvent can be recycled, significantly reducing preparation costs.
[0035] The above description shows the main features, basic principles, and advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments or examples, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, the above embodiments or examples should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims be included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved. Any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the technical principle of the present invention should fall within the scope of patent protection of the present invention.
Claims
1. A method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material, characterized in that: The steps include: S1. Grinding biomass waste into short fibers, then treating them with a three-component deep eutectic solvent of zinc chloride / phosphoric acid / ammonium dihydrogen phosphate at room temperature to prepare nanocellulose, filtering and washing them, soaking them in deionized water, and then stirring them to form a stable gel-like fiber suspension; S2. Add polyvinyl alcohol to deionized water and dissolve the mixture in a water bath to obtain a polyvinyl alcohol solution; add chitosan to the acetic acid solution, dissolve the mixture and stir to obtain a chitosan solution; S3, reacting methyltrimethoxysilane / tetramethoxysilane in a ratio of 1:10 to 10:1 at 300 r / min, 30°C, and pH = 9 for 1 h to prepare a methyltrimethoxysilane / tetramethoxysilane copolymer emulsion with a concentration of 5%; S4. Place the gel-like fiber suspension obtained in S1, the polyvinyl alcohol solution obtained in S2, and the chitosan solution obtained in S2 in a conical flask, add sodium dodecyl sulfate, titanium dioxide, and ferrosoferric oxide, stir to foam, then add the methyltrimethoxysilane / tetramethoxysilane copolymer emulsion obtained in S3 and continue stirring, pour the completely foamed wet foam into a mold, let it stand at room temperature, and then dry to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material; by alternately using water and ethanol for solvent exchange at 80°C, the reversible hydrophilic / hydrophobic switching of the magnetic biomass foam material is achieved.
2. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 1, wherein: The fiber content of the biomass waste in S1 is 50%-85%, and the biomass waste is ground into 60-80 mesh short fibers.
3. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 2, wherein: The molar ratio of the zinc chloride / phosphoric acid / ammonium dihydrogen phosphate three-component deep eutectic solvent in S1 is 1:0.3:1 to 1:0.3:
6.
4. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 3, wherein: After filtering and washing, the S1 was immersed in 200 mL of deionized water for 24 h, and then stirred at 2000-4000 r / min for 10-30 min to form a stable gel-like fiber suspension.
5. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 1, wherein: In the S2, 2-8 g of polyvinyl alcohol is added to deionized water at a ratio of 1:8-1:20, and the mixture is dissolved in a water bath at 90° C. at a rotation speed of 500 r / min to obtain a polyvinyl alcohol solution.
6. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 5, characterized in that: In the S2, 0.2-1 g of chitosan is added to 50 mL of 2% acetic acid solution, dissolved and stirred for 30 min to obtain a chitosan solution.
7. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 1, wherein: In the S4, the fiber suspension obtained in S1, the polyvinyl alcohol solution obtained in S2, and the chitosan solution obtained in S2 are placed in a conical flask, sodium lauryl sulfate, titanium dioxide, and ferrosoferric oxide are added, and stirred to foam, and then the methyltrimethoxysilane / tetramethoxysilane copolymer emulsion with a concentration of 5% obtained in S3 is added and continued to be stirred, and the completely foamed wet foam is poured into a mold, allowed to stand at room temperature, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material; under mild conditions, the solvent is exchanged by alternating between water and ethanol to achieve reversible hydrophilic / hydrophobic switching of the magnetic biomass foam material.
8. The method for preparing a reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 7, characterized in that: In the S4, the fiber suspension obtained in S1, the polyvinyl alcohol solution obtained in S2, and the chitosan solution obtained in S2 are placed in a 500 mL conical flask, 0.2-1.0 g of sodium lauryl sulfate, 0.5-3.5 g of titanium dioxide, and 1-5 g of ferrosoferric oxide are added, and the mixture is stirred at 3000 r / min for 15-30 min to foam. Then, 20-50 g of 5% methyltrimethoxysilane / tetramethoxysilane copolymer emulsion obtained in S3 is added and continued to be stirred for 10 min. The completely foamed wet foam is poured into a mold, allowed to stand at room temperature for 30 min, and then dried to obtain a reversibly hydrophilic / hydrophobic modified magnetic biomass foam material; by alternately using water and ethanol for solvent exchange at 80°C, the reversible hydrophilic / hydrophobic switching of the magnetic biomass foam material is achieved.
9. A reversible hydrophilic / hydrophobic magnetic biomass foam material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the reversibly hydrophilic / hydrophobic magnetic biomass foam material according to claim 9 in sewage treatment.
Citation Information
Patent Citations
Composite photo catalytic sewage treating material and its prepn
CN100351011C
Preparation method and application of magnetic response multifunctional super-hydrophobic biomass aerogel
CN119186420A
Cited By
Photoelectric thermomagnetic control biomass composite material with simple wettability switching prepared by water-phase one-pot method and application of photoelectric thermomagnetic control biomass composite material
CN120695797A